Under Pressure: Electoral Competition and Women's Representation - Pamela Campa; Perihan Saygin; Semih Tumen (Institute of Labor Economics (IZA), 2024)
How can women's representation improve in countries that do not embrace legislated gender quotas? We study municipal elections in Turkey during 2009-2019. A conservative dominant party, Erdogan's AKP, is often challenged by a Kurdish party that promotes gender equality in electoral lists. Exploiting within-municipality variation, we find that the Kurdish party winning leads AKP to increase its share of female candidates by 25 to 30% in the next election. Other opposition parties winning has a substantially lower impact. Our results suggest that one party empowering women can help reducing gender gaps in lists across-the-board.
Keywords: D72; J16; 330; women political representation; electoral competition